Analysis of the Effect of Perceived Ease of Use and Perceived Usefulness on E-reader Use with User Satisfaction as an Intervening Variable on @Basebuku Followers in X - Siti Hidayatul Khoirun Nisa'; Nurhadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of Perceived Ease of Use and Perceived Usefulness on e-reader usage, with User Satisfaction as an intervening variable, among followers of the @basebuku account on the X platform. This study employs a quantitative approach, using a questionnaire to collect data from 168 respondents selected via purposive sampling. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results indicate that Perceived Ease of Use and Perceived Usefulness have a positive and significant effect on User Satisfaction. Perceived Ease of Use has a positive but not significant effect on e-reader usage, while Perceived Usefulness and User Satisfaction have positive and significant effects on ereader usage. Additionally, User Satisfaction was found to significantly mediate the effects of Perceived Ease of Use and Perceived Usefulness on e-reader usage. These findings indicate that user satisfaction plays a crucial role as a mediating factor in driving e-reader usage. Therefore, enhancing the perceived ease of use and perceived usefulness for users needs to be optimized to increase both satisfaction and e-reader usage.